Exploring the efficacy of cannabinoids in the management of multiple sclerosis - Aleksandra Rykucka; Natalia Zozula; Marcin Wąs; Justyna Kiełbasa; Agata Kowalczyk; Katarzyna Bil; Iga Ślesicka; Aleksandra Latała; Zuzanna Tomczewska; Magda Przestrzelska (Kazimierz Wielki University, 2024)
Introduction: Multiple Sclerosis (MS) is a chronic autoimmune disease of the central nervous system, marked by inflammation, demyelination, and neurodegeneration. It severely impacts quality of life with symptoms like spasticity, pain, and cognitive impairment. Conventional treatments often fail, necessitating alternative therapies. Purpose: This review evaluates the efficacy and safety of cannabis extracts in treating MS, enhancing understanding of their benefits and limitations. State of knowledge: Studies suggest that cannabinoids may alleviate MS symptoms, particularly spasticity and pain. Clinical trials have shown significant reductions in muscle stiffness and pain, along with improved sleep quality. Meta-analyses, by Whiting et al. and Cochrane, support these findings but highlight the risk of side effects, which may limit long-term use. Additionally, research on animal models and in vitro studies indicate that cannabinoids may have neuroprotective and immunomodulatory properties, potentially reducing neuroinflammation and demyelination. Conclusion: Cannabinoids exhibit potential as a complementary therapy for managing MS symptoms, especially spasticity and pain. However, evidence is mixed, with some studies showing limited efficacy and considerable risk of side effects. More long-term, high-quality studies are needed to fully understand the therapeutic potential and safety profile of cannabinoids in MS treatment. Despite the challenges, the growing availability and changing legal status of medical cannabis suggest it could be a viable option for some patients, provided its use is carefully monitored and adapted to individual needs.